Microwave Assisted Synthesis Spectral and Antibacterial Investigations on Complexes of Mn(II) With Amide Containing Ligands - N. Bhojak; D. D. Gudasaria; N. Khiwani; R. Jain (E-Journal of Chemistry)
The present research work describes the synthesis, spectral and antibacterial studies on the complexes of Mn(II) with amide group containing ligands. Synthesis of complexes has been carried out by conventional method as well as by microwave method. The complexes have been characterized on the basis of elemental analysis, infrared, electronic spectra and magnetic susceptibility studies. The diffuse reflectance spectrums of the complexes show bands in the region 20,000 cm-1 to 26,000 cm-1 assignable to 6A1g → 4T2g and 6A1g → 4E1g transitions. These are also typical of tetrahedral environment around the manganese. The magnetic moment (5.80 BM) of the complex indicates high spin tetrahedral environment. The microwave method of synthesis of complexes have been found easier, convenient and ecofriendly.